The physics book : from the big bang to quantum resurrection, 250 milestones in the history of physics - Pickover, Clifford A. (Sterling, 2011)
Chronicles 250 milestones in the history of physics, explaining major concepts, and featuring brief entries on dark energy, parallel universes, the Doppler effect, the God particle, and other related topics.